Limitele temporale ale dreptului la viață - Pozneacova, Veronica; Zaharia, Virginia (Tipografia „Adrilang”, 2022)
Life represents a constitutional right, regulated at the International and national levels. Despite of the general importance of this fundamental right, the moment of the emergence and extinction of the right to life remains a controversial one, both in the doctrinal discussions and in the debates of the wide circles of the population. The birth and death of a person, facts that have the legal connotation form the temporal limits of the right to life being presented within the current regulations. States have not adopted a unanimously recognized vision on the emergence of the right to life in aspects related to the legal status of the embryo and that of the unborn child. The substantial difference between the legislations of several states is manifested in the establishment of conception or birth as the beginning from which the life of the human being enjoys the protection of the state. The death, as the temporal limit of the right to life in the present, generates many discussions with ethical, legal and medical connotation. Currently, the establishment of the person’s death is based on the criterion of biological death or brain death. Introducing brain death as a basic criterion for ascertaining death determined the necessity to justify it from the perspective of ascertaining the cessation of brain activity or certain areas of it, being closely related to the field of transplantology. The purpose of this article is to determine the models of regulation of the temporal limits of the right to life, as well as to analyze the specifics of each approach based on medical, ethical, philosophical and legal arguments.

Viața reprezintă un drept constituțional, apărat la nivelul internațional și cel național. În pofidă importanței general umane a acestui drept fundamental, momentul apariției și stingerii dreptului la viață rămâne unul polemizat, atât în cadrul discuțiilor doctrinare, cât și în dezbaterile cercurilor largi ale populației. Nașterea și moartea unei persoane, fapte cu caracter juridic, care formează limitele temporale ale dreptului la viață, au o conotației specifică în cadrul reglementărilor actuale. Statele nu au adoptat o viziune unanim recunoscută referitor la apariția dreptului la viață în aspectele legate de statutul juridic al embrionului și cel al copilului nenăscut. Diferența substanțială între legislațiile mai multor state se manifestă prin stabilirea concepției sau nașterii ca începutul de la care viața ființei umană se bucură de protecția statului. Constatarea morții, ca limitei temporale a dreptului la viața în prezent trezește mai multe discuții în jurul unor concepte cu conotație etică, juridică și medicală. În prezent, constatarea morții se efectuează, bazându-se pe criteriul morții biologice sau a morții cerebrale. Introducerea morții creierului ca fiind un criteriu de bază pentru constatarea morții a determinat necesitatea argumentării acestuia din perspectiva procesului de constatare a încetării activității creierului sau a anumitor zone ale acestuia, fiind strâns legată de domeniul transplantologiei. Scopul articolul dat este determinarea modelelor de reglementare a limitelor temporale ale dreptului la viață, cât și elucidarea specificului fiecărei abordări bazate pe argumentele de ordin medical, etic, filosofic și juridic.
Keywords: life; unborn child; biological death; brain death; human rights; viață; copilul nenăscut; moartea biologică; moartea cerebrală; drepturile omului